SENAM EFEKTIF MENURUNKAN KADAR GULA DARAH PASIEN DM TIPE 2 - Jati Ekawati; Aris Mahfud (MEDIA ILMU KESEHATAN, 2013)
Background: Diabetes is one of the major threats to human health in the 21st century. Indonesia's own country with diabetes mellitus was ranked the world's fourth largest with 8.6% of the total prevalence of diabetes sufferers after India, China, and the United States. Factors that influence diabetes include; 1) age, 2) Obesity, 3) Family History, and 4) ethnic group. There are four pillars of prevention in Indonesia which is applied to the diabetes to control blood sugar levels, namely: 1) diet, 2) Physical Exercise, 3) medications, and 4) Health Education. Objective: To determine the effect of physical exercises Gymnastic DM administration and Gymnastic Senior to decrease blood sugar levels in patients with type 2 diabetes. Method: This study is a quantitative study with this type of study without a comparison group quasy experiments. The design of the study is a pretest-posttest one group design. Number of samples used were 41 respondents from the participants calisthenics DM in the psychiatric hospital. Prof. dr. Soerojo Magelang. Analysis of the data used is the analysis bivariabel univariabel and analysis using statistical models Paired sample t-tests with significance level α = 0.05. Result: There was a decrease in blood sugar levels after exercise DM for 3 times a week for 2 weeks, an average of 64.780 mg/dl. T count value obtained at 13.624 with a p-value 0.000 <0.05, means that there are significant differences in blood sugar levels before and after doing gymnastic DM and Gymnastic Senior. Conclusion: The provision of physical training exercises conducted by DM DM participants calisthenics in Prof. RSJ. Dr. Soerojo Magelang for 3 times a week for 2 weeks can lower blood sugar levels in patients with type 2 diabetes mellitus. Keywords: Physical exercise, gymnastics, blood sugar levels.